Synthesis and characterization of bionanocomposite silver nanoparticles (AgNPs)-chitosan/polylactic acid (PLA) biofilm - Aznizan, Shaari (2014)
Biobased polymers derived from renewable resources are increasingly important due to intense concerns about the environmental issues and limited petrol eum resources. Poly(lactic acid) (PLA) is such polymer that has shown good potential to produce biodegradable plastics. However, poor antimicrobial and mechanical properties restrict its broad applications. The thesis pursues to overcome these limitations by blending PLA with chitosan and reinforcing them with inorganic nanoparticles. The performances of antimicrobial biodegradable films with enhanced properties have potential good for many applications. Firstly, the silver nanoparticles have been synthesized with tea extract leaves. Characterization of silver nanoparticles by UV-vis, TEM, XRD and FTIR indicate that silver nanoparticles were present in the tea extract solution with the range of size 10-150 nm. Antimicrobial analysis of silver nanoparticles against gram negative (Escherichia coli) and gram positive (Micrococcus luteus) microorganisms had proved that silver nanoparticles is a good antimicrobial agent although incorporated with blending of PLA/chitosan films. The best concentration of silver nanoparticles which incorporated with PLA/chitosan films was 23.08% w/w. It means that films have showed slight growth of microorganism at 23.08% w/w of silver nanoparticles.The films were characterized by FESEM and EDX. The morphological images presented the shape of silver nanoparticles incorporated into the films was almost spherical. Tensile measurement was represented by tensile strength and elongations at break which were used as a response for choosing of the best conditions bionanocomposite films fabrication (BFF) in the mechanical properties films. The interaction and main effect of two factors with the range (0-30%) concentration of plasticizer PEG and (0-100%) percentage volume PLA/chitosan were studied using 2level